The 24th International Electronic Conference on Synthetic Organic Chemistry 2020
DOI: 10.3390/ecsoc-24-08419
|View full text |Cite
|
Sign up to set email alerts
|

Study of 1,2,4-triazole-3(5)-thiol Behavior in Reactions with 1-phenyl-1H-pyrrole-2,5-dione Derivatives and 3-bromodihydrofuran-2(3H)-one and Antimicrobial Activity of Products

Abstract: In present work we report our studies of the interaction of 1-phenyl-1H-pyrrole-2,5-dione derivatives (N-arylmaleimides) and 3-bromodihydrofuran-2(3H)-one (α-bromo-γ-butyrolactone) as possible [C2] 2+ synthons with 1,2,4-triazole-3(5)-thiole targeting on synthesis of novel 5substituted thiazolo[3,2-b][1,2,4]triazole-6-ones. According to obtained results was establish that in above-mentioned interactions (conditions: convenient heating, range of solvents/reaction time) the thiol-ene click (for N-arylmaleimides)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The reaction of N-arylmaleimides with heterocyclic 1,3-N,S-binucleophiles (for example, 2-thioquinazolines [7] and 2-mercapto-1,2,4-triazoles [5]) leads to the formation of condensed systems, such as thiazolo [2,3-b]quinazolines and thiazolo [3,2-b] [1,2,4]triazoles, respectively. Thioethers-products of sulfur atom addition to the double bond of N-arylmaleimides by the Michael reaction type were isolated for 2-mercapto-1,2,4-triazole [6].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reaction of N-arylmaleimides with heterocyclic 1,3-N,S-binucleophiles (for example, 2-thioquinazolines [7] and 2-mercapto-1,2,4-triazoles [5]) leads to the formation of condensed systems, such as thiazolo [2,3-b]quinazolines and thiazolo [3,2-b] [1,2,4]triazoles, respectively. Thioethers-products of sulfur atom addition to the double bond of N-arylmaleimides by the Michael reaction type were isolated for 2-mercapto-1,2,4-triazole [6].…”
Section: Resultsmentioning
confidence: 99%
“…The addition of S-nucleophiles by the Michael reaction to the double bond of N-substituted maleimides is widely used in organic synthesis [24][25][26][27]. Similar intermediates are also formed in reactions with other binucleophilic substrates [6,19,21].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lesyk R. et al [42], as a result of boiling an equimolar mixture of reagents for 2 h in acetic acid, were able to isolate N-(R-phenyl)-(6-oxo-5,6-dihydro [1,3]thiazole [3,2-b] [1,2,4]triazol-5-yl)acetamides 51 based on the example of 1,2,4-triazole-3(5)-thiol 50. However, S. Holota [43], when investigating the same interaction, showed that boiling an equimolar mixture in the range of 30 min-24 h and the use of such solvents as acetic acid, acetone, acetonitrile, benzene, and toluene in the presence or absence of sodium acetate only led to the formation of linearly-bound product 52. At the same time, attempts at the cyclization of 52 did not lead to success.…”
Section: Reactions With S-and O-containing Dinucleophilesmentioning
confidence: 99%